The Role of Occupational Health and Safety Procedures in Reducing Occupational Diseases within the Workplace: Souq Al-Khamis Cement and Building Materials Complex as a Model - أ. ملاك نوري نصير (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aims to evaluate the actual impact of occupational health and safety programs in reducing the spread of occupational diseases among workers at the Souq Al-Khamis Cement Factory in Libya. The research problem arises from the clear contradiction between the formal existence of such programs and the continued recording of work-related diseases and injuries, raising a fundamental question about their true practical effectiveness. The importance of the study lies in filling part of the gap in local and Arab literature and providing factory management and regulatory bodies with accurate diagnosis and field data to support informed decision-making for improving the work environment. The study sought to answer a main question regarding the actual impact of these programs, with sub-questions exploring the nature of the applied programs, the prevalence of occupational diseases, workers’ evaluation of their effectiveness, and the obstacles facing implementation. The main hypothesis tested was the existence of a statistically significant negative correlation between the evaluation of program effectiveness and the prevalence of diseases, alongside several sub-hypotheses addressing demographic differences and the relationship between program dimensions and injury rates. The study adopted the descriptive analytical method and applied a questionnaire to a stratified random sample of 70 workers from a study population of 566. The key findings revealed major shortcomings in workers’ evaluation of program effectiveness, with only 32.86% agreeing on their overall effectiveness. Results also showed a noticeable prevalence of occupational diseases, with 27.14% of the sample officially diagnosed, and the highest rates recorded for respiratory symptoms (38.57%) and musculoskeletal disorders (50%). The study identified obstacles to implementation, including administrative barriers (68.57%), lack of resources (60.00%), and human-related challenges (54.29%). Statistical analyses confirmed a strong, significant inverse correlation between program evaluation and the prevalence of health symptoms (correlation coefficient = -0.423). Regression analysis indicated that evaluation explained 17.9% of the variance in disease prevalence. Based on the results, the study recommended the development of a clear occupational health and safety policy, the design of intensive and practical training programs, provision of adequate and appropriate personal protective equipment, activation of strict monitoring and supervisory